2005
DOI: 10.1083/jcb.200403078
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically inactive human cathepsin D triggers fibroblast invasive growth

Abstract: The aspartyl-protease cathepsin D (cath-D) is overexpressed and hypersecreted by epithelial breast cancer cells and stimulates their proliferation. As tumor epithelial–fibroblast cell interactions are important events in cancer progression, we investigated whether cath-D overexpression affects also fibroblast behavior. We demonstrate a requirement of cath-D for fibroblast invasive growth using a three-dimensional (3D) coculture assay with cancer cells secreting or not pro-cath-D. Ectopic expression of cath-D i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 50 publications
7
98
1
1
Order By: Relevance
“…Excess M6P prevented pro-cath-D from binding to its M6P receptors and inhibited the internalization of pro-cath-D by 82% ( Figure 1A, panel a, compare lanes 1 and 3). Thus, 18% of pro-cath-D was taken up by HMF fibroblasts in a manner that was independent of the M6P receptors ( Figure 1A, panel a, lane 3), as shown for mouse fibroblasts (Laurent-Matha et al, 2005). Inhibiting LRP1 synthesis with siRNA ( Figure 1A, panel b) led to a 50% decrease in reminiscent pro-cath-D internalization ( Figure 1A, panel a, compare lanes 3 and 4).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Excess M6P prevented pro-cath-D from binding to its M6P receptors and inhibited the internalization of pro-cath-D by 82% ( Figure 1A, panel a, compare lanes 1 and 3). Thus, 18% of pro-cath-D was taken up by HMF fibroblasts in a manner that was independent of the M6P receptors ( Figure 1A, panel a, lane 3), as shown for mouse fibroblasts (Laurent-Matha et al, 2005). Inhibiting LRP1 synthesis with siRNA ( Figure 1A, panel b) led to a 50% decrease in reminiscent pro-cath-D internalization ( Figure 1A, panel a, compare lanes 3 and 4).…”
Section: Resultsmentioning
confidence: 58%
“…We checked these results by investigating the effect of recombinant proteolytically inactive D231N pro-cath-D on the production of endogenous LRP1b-CTF in HMF .1(-) plasmids using Lipofectamine (Gibco-BRL, Life Technologies SAS, Villebon sur Yvette, France). pcDNA3.1(-)cath-D expression plasmid encoding human pre-pro-cath-D has previously been described (Vignon et al, 1986;Glondu et al, 2001Glondu et al, , 2002Berchem et al, 2002;Laurent-Matha et al, 2005;Hu et al, 2008). fibroblasts ( Figure 3C, panel a).…”
Section: Ectopic Cath-d and Pro-cath-d Inhibit Lrp1 Rip In Cos Cells mentioning
confidence: 99%
See 2 more Smart Citations
“…5 In addition, it has been suggested that the expression of lysosomal cathepsins are substantially increased in malignant tumours. 6 Furthermore, lysosomal cathepsins can also be produced by stromal fibroblasts and inflammatory cells, which are believed to produce cytokines and proteins that induce the production of cathepsins. The excessive expression and activity of cathepsisns not only helps in promoting tumour growth by increasing the bioavailability of growth factors that reside in the ECM, but also enhances degradation of the ECM components that promote tumour cell invasion, metastasis and the formation of secondary tumours.…”
mentioning
confidence: 99%